Faktor-Faktor yang Mempengaruhi Dana Pihak Ketiga pada Bank Umum Syariah di Indonesia Tahun 2010-2022 - Nurul Jannah; Ima Amaliah (UNISBA Press, 2024)
Abstract. Third Party Funds (DPK) have an important role for banks, because third party funds are a source for banks in channeling financing to third parties as wellas for other asset allocations. This study aims to determine the effect of the numberof offices, profit sharing, inflation, and LPE on (DPK) at Islamic CommercialBanks in Indonesia in 2010-2022. The type of research used is descriptive quantitative with averification approach. The data used is secondary data, namely annual data from 2010-2022which consists of DPK, number of offices, and Profit Sharing of IslamicCommercial Banks as well as macroe-conomic variables, namely inflation and LPE.Secondary data was obtained from the official publication of the IndonesianFinancial Services and Statistics Authority website from the Central Bureau of Statistics. Data processing uses the Eviews program version 9.0 with the OrdinaryLeast Square (OLS) method. From the results of model estimation, the independent variables thatpartially affect DPK are the number of offices and profit sharing because theprobability value is less than 0.05 and 0.1. Meanwhile, LPE and inflation partiallyaffect DPK in Islamic Commercial Banks in Indonesia. However, together thenumber of offices, profit sharing, inflation and LPE have an effect on DPK atIslamic Commercial Banks in Indonesia. The results of the study show that thenumber of offices, profit sharing, inflation and LPE all have an effect on Third Party Funds (DPK) . The large variation in the variable number of offices, profit sharing,inflation and LPE on DPK was 77.09% while the rest was due to variations in othervariables not included in the study. Abstrak. Dana Pihak Ketiga (DPK) memiliki peranan penting bagi bank, karena dana pihak ketiga merupakan sumber bagi bank dalam menyalurkan pembiayaan kepadapihak ketiga serta untuk alokasi asset lainnya. Penelitian ini bertujuan untukmengetahui pengaruhjumlah kantor, bagi hasil, inflasi, dan LPE terhadap (DPK)pada Bank Umum Syariah di Indonesia Tahun 2010-2022. Jenis penelitian yang digunakan adalah deskriptif kuantitatif dengan pendekatan verifikatif. Data yang digunakan adalah data sekunder yaitu datatahunan dari 2010-2022 yang terdiriatas DPK, jumlah kantor, dan Bagi Hasil Bank Umum Syariah serta variabel makroekonomi yaitu inflasi dan LPE. Data sekunder diperoleh dari publikasi resmi website Otoritas Jasa Keuangan dan Statistik Indonesia dari Badan Pusat Statistik. Pengolahan data menggunakan program Eviews versi 9.0 dengan metode ordinary Least Square (OLS). Dari hasil estimasi model, variabel independent yang secara parsialberpengaruh terhadap DPK adalah jumlah kantor dan bagi hasil karena nilaiprobabilitanya lebih kecil dari 0,05 dan 0,1. Sedangkan LPE dan inflasi secaraparsialberpengaruh terhadap DPK pada Bank Umum Syariahdi Indonesia. Namundemikian secara bersama-sama jumlah kantor, bagi hasil, inflasi dan LPE berpengaruh terhadap DPK pada Bank Umum Syariah di Indonesia.Hasil penelitian menunjukkan bahwa jumlah kantor, bagi hasil, inflasi dan LPE secarabersama-samaber pengaruh terhadap Dana Pihak Ketiga (DPK). Adapun besarnyavariasi variabel jumlah kantor, bagi hasil, inflasi dan LPE terhadap DPK sebesar77,09% sedangkan sisanya karena variasi dari variabel lain yang tidak dimasukkan dalam penelitian.